Elementary Numeracy Patterns by Initial Mathematical Ability: Pola Numerasi Siswa Berdasarkan Kemampuan Awal Matematis - Sundari, Sundari; R. Habibie, Zulqoidi; Subhanadri, Subhanadri (Academia Open, 2026)
General Background Numeracy is a fundamental competence in elementary education because it enables students to interpret numbers, reason logically, and solve contextual mathematical problems. Specific Background Word problems require students not only to calculate but also to understand contexts, identify relevant information, select appropriate operations, and organize solution steps systematically. Knowledge Gap Previous studies have largely emphasized learning outcomes or instructional models, while limited attention has been given to how students’ numeracy profiles, thinking processes, and difficulties differ according to their initial mathematical ability. Aims This study analyzes elementary students’ numeracy ability in solving word problems based on initial mathematical ability and identifies the characteristics and difficulties found in high, moderate, and low ability categories. Results Students with high initial mathematical ability demonstrated integrated skills in reading problems, organizing information, selecting strategies, and presenting systematic solutions. Students with moderate ability showed adequate but inconsistent numeracy performance, particularly in processing complex information and presenting accurate answers. Students with low ability experienced fundamental difficulties in understanding problem contexts, choosing operations, and avoiding number grabbing strategies. Novelty This study provides a differentiated analysis of numeracy by examining final answers, solution processes, error patterns, and ability characteristics across initial mathematical ability levels. Implications Numeracy instruction should integrate reading literacy with basic mathematical concepts and apply differentiated contextual learning according to students’ initial ability profiles. Highlights • High-performing students showed systematic reasoning in interpreting word problems.• Moderate-performing students completed tasks adequately but lacked consistency.• Low-performing students struggled with context, operations, and structured reasoning. Keywords Numeracy; Word Problems; Mathematical Reasoning; Contextual Learning; Elementary Students